Racionalismo y tradición escolar en el "Arte" de Nebrija reformado por el P. Juan Luis de la Cerda - Martínez Gavilán, María Dolores (Península: revista de estudos ibéricos, 2007)
The need to unify Latinity studies in Spain resulted in the imposition of a reformed version of Nebrija's Introductiones Latinae as the official, compulsory text to be used in universities and other teaching institutions.The revision of Nebrija's text was carried out by Father Juan Luis de la Cerda (De institutione grammatica libri quinque) and focussed on its theoretical and methodological aspects, which this article seeks to analyse. On the one hand, the practical aspects of several pedagogical resources are explored - some of which were very closely related to Latin didactics - and, on the other hand, attention is drawn to the author's attempt to renovate the doctrine by incorporating the postulates established in Francisco de las Brozas.